Clinical research in neonates and infants: Challenges and perspectives. (June 2016) - Coppini, Raffaele; Simons, Sinno H.P.; Mugelli, Alessandro; Allegaert, Karel
Abstract: To date, up to 65% of drugs used in neonates and infants are off-label or unlicensed, as they were implemented in clinical care without the usual regulatory phases of pharmacological drug development. Pharmacotherapy in this age group is still mainly based on the individual clinical expertise of specialized pediatricians. Pharmacological trials involving neonates are indeed more difficult to perform: appropriate dosing is hampered by the rapid physiological changes occurring at this stage of development, and the selection of proper end-points and biomarkers is complicated by the limited knowledge of the pathophysiology of the specific diseases of infancy. Moreover, there are many ethical challenges in planning and conducting drug studies in pediatric patients (especially in newborns and infants). In the current review, we address some challenges and discuss possible perspectives to stimulate scientific and clinical pharmacological research in neonates and infants. We hereby aim to illustrate the add on value of the regulatory framework for model-based neonatal medicinal development currently used in Europe and the United States. We provide several examples of successful recent pharmacological trials performed in neonates and infants. In these examples, success was ensured by the implementation of specific pharmacokinetic assessments, thanks to accurate drug dosing achieved with a combination of dose validation, population pharmacokinetics and mathematical models of drug clearance and distribution; moreover, age-specific pharmacodynamics was considered via appropriate evaluations of drug efficacy with end-points adapted to the peculiar pathophysiology of diseases in this age group. These "pharmacological" challenges add to the ethical challenges that are always present in planning and conducting clinical studies in neonates and infants and support the opinion that clinical research in pediatrics should be evaluated by ad hoc ethical committees with specific expertise.